The Developmental Stages and Theoretical Foundations of Satire as a Literary Genre - Abdullayev, Shavkatjon (The Lingua Spectrum, 2025)
This article presents information on the developmental stages and theoretical foundations of satire as a literary genre. In order to provide readers with a clear understanding of the historical roots of satire, existing definitions and interpretations concerning its origins are compiled and analyzed in depth to reach well-grounded conclusions. Special attention is given to the terminology of satire, offering a comprehensive overview of definitions. Based on these scholarly definitions, readers will acquire a certain level of theoretical understanding regarding the emergence of the satirical genre. The article explores the sequential stages of satire’s evolution as a literary form, examining key events and contextual details relevant to each stage. Moreover, the factors that contributed to the formation of satire during phases are discussed, with particular emphasis on the historical circumstances and influential elements that enhanced the significance of satire. By reading this article, readers will also gain insight into notable and rare works created throughout the developmental history of satire as a literary genre.